Adverse reactions to antirretroviral drugs in patients with the human inmunodeficiency virus - Neity Mendo Alcolea; Eduardo de Jesús Mesa Perez; Rafael Neyra Barrios; Lázaro Berenguer Gournaluses; Graciela Nieto Muñiz (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive and cross sectional study of 40 patients with HIV belonging to the Teaching Polyclinic "Frank País García" in Santiago de Cuba was carried out with the aim of identifying the adverse reactions to antirretroviral drugs during the first semester of 2018. Most of the notifications were carried out by specialists in Comprehensive General Medicine (61,4%) in the case material, followed by those of Internal Medicine and  Licentiate in Nursing (8,8 and 17,6%, respectively); also, among the predominant adverse effects there were nauseas, migraine and sickness, fundamentally with the therapeutic schemes constituted by lamivudina-zidovudina-nevirapina and zidovudina-nevirapina-efavirenz.  It is concluded that during antirretroviral treatment most of these reactions were classified as definitive, independently of the prescribed therapeutic scheme and the concomitant diseases.